2020
DOI: 10.21203/rs.3.rs-26672/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atorvastatin Promotes Bone Formation in Aged apoE–/– Mice through the Sirt1–Runx2 Axis

Abstract: Background: Statins are the most widely used drugs in elderly patients, the most common clinical application of statins is in aged hyperlipemia patients. There are few studies on the effects and mechanisms of statins on bone in elderly mice with hyperlipemia. The study is to examine the effects of atorvastatin on bone phenotypes and metabolism in aged apolipoprotein E-deficient (apoE–/–) mice, and the possible mechanisms involved in these changes. Methods: Twenty-four 60-week-old apoE–/– mice were randomly all… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Runx2 haploinsufficiency leads to the skeletal disorder characterized by bone and dental abnormalities known as cleidocranial dysplasia [70]. Hong et al found that atorvastatin increases bone mass and promotes osteogenesis in ageing apolipoprotein E-deficient mice by activating SIRT1-Runx2 axis [71]. Additionally, Res increases the formation of SIRT1 and FOXO3a complex, regulates the activity of Runx2 promoter, and promotes ossification of human MSCs [72].…”
Section: Osteoblasts and Osteoclastsmentioning
confidence: 99%
“…Runx2 haploinsufficiency leads to the skeletal disorder characterized by bone and dental abnormalities known as cleidocranial dysplasia [70]. Hong et al found that atorvastatin increases bone mass and promotes osteogenesis in ageing apolipoprotein E-deficient mice by activating SIRT1-Runx2 axis [71]. Additionally, Res increases the formation of SIRT1 and FOXO3a complex, regulates the activity of Runx2 promoter, and promotes ossification of human MSCs [72].…”
Section: Osteoblasts and Osteoclastsmentioning
confidence: 99%